Extending Photography: the Meta-Medial/Conversational Layers of Dematerialized Photographs. (3rd July 2019) - Eid-Sabbagh, Yasmine
Abstract: This article contemplates a collection of digital photographs gathered in Burj al-Shamali, a Palestinian refugee camp in Lebanon, between 2001 and 2011. It uses an arts-based research practice in which photographs are treated as multi-layered substances, composed of a stratified physical object with different meta-medial layers, in order to consider the ethical, theoretical and practical challenges of capturing the emotions, subjectivities, experiences and politics that exceed the material image within the collection itself. These diverse narratives and active layers, which overlay a photograph's embodied material layers, are called meta-medial layers. Considering photographs in this way is to recognize a certain fragility, and opens up the possibility of emancipating these same photographs from dominant readings. By looking at how photographs were gathered in Burj al-Shamali camp on the one hand, and distributed in their dematerialized form through performative interventions on the other, this article considers how the meta-medial dimension – and particularly the conversational aspect – of these photographs constitutes a practice of collective self-determination.